The Contribution of Hajj and Umrah Development to MSME Growth in Indonesia: A Systematic Literature Review - Budi Nurdian; Dinni Agustin; Tina Rosa; Kwarnanto; Sri Siswani (Asian Journal of Social and Humanities, 2026)
The development of the Hajj and Umrah industry in Indonesia has generated significant economic impacts, particularly for Micro, Small, and Medium Enterprises (MSMEs). As the country with the largest Muslim population in the world and one of the largest contributors of Hajj and Umrah pilgrims annually, Indonesia has experienced rapid growth in religious tourism-related economic activities. This research aims to systematically review the existing literature regarding the contribution of Hajj and Umrah development to MSME growth in Indonesia. Using the Systematic Literature Review (SLR) approach guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, this study synthesizes findings from national and international scientific publications indexed in databases such as Scopus, Google Scholar, Dimensions, and Web of Science. A total of 78 eligible studies were included and critically appraised using a risk-of-bias assessment framework. The review identifies major themes, including economic multiplier effects, MSME empowerment, halal industry development, digital transformation, employment generation, and challenges faced by MSMEs within the Hajj and Umrah ecosystem. The findings indicate that the Hajj and Umrah sectors contribute substantially to local economic development through increased demand for halal products, accommodation services, transportation, culinary services, Muslim fashion, and pilgrimage support services. However, MSMEs continue to face challenges related to digitalization, financial access, product standardization, and market competition. This study provides a conceptual synthesis of the relationship between religious tourism and MSME development and offers recommendations for policymakers, industry practitioners, and future researchers.